1995
DOI: 10.1002/1097-0142(19950601)75:11<2669::aid-cncr2820751105>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular carcinoma during pregnancy and its comparison with other pregnancy-associated malignancies

Abstract: Background. Cancer in pregnancy is rare and hepatocellular carcinoma (HCC) in pregnancy even rarer. The impact of pregnancy on the prognosis of patients with different types of cancer remains controversial. Reported cases of HCC in pregnancy are largely isolated and highly scattered. Thus, the effect of pregnancy on the prognosis of patients with HCC and the risk factors of developing HCC in pregnancy are not well documented. Methods. A series of five patients with HCC in pregnancy seen at two different center… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
67
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(70 citation statements)
references
References 43 publications
2
67
0
Order By: Relevance
“…The risk of HCC rises with increasing parity [27]. Involvement of the liver may affect coagulation function, which should be assessed before regional anesthesia is administered.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of HCC rises with increasing parity [27]. Involvement of the liver may affect coagulation function, which should be assessed before regional anesthesia is administered.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of HCC is low in young women (3/100 000 per year at age below 40, Hong Kong Cancer Registry 1996) and less than 40 cases of HCC complicating pregnancy have been reported worldwide, including 12 cases in Chinese. 8 The outcome is invariably poor, with few maternal survivals. This is attributed to delayed diagnosis, estrogen stimulation of HCC growth and preg- nancy-related immunotolerance.…”
Section: Discussionmentioning
confidence: 99%
“…This is attributed to delayed diagnosis, estrogen stimulation of HCC growth and preg- nancy-related immunotolerance. 8 Abdominal distension and raised AFP levels during pregnancy can cause diagnostic difficulty. 9 Estrogen stimulation of HCC growth is probably not a factor in our case with negative receptor staining.…”
Section: Discussionmentioning
confidence: 99%
“…By 1995 there were approximately 30 reported cases of HCC during pregnancy [101], whereas a more recent review of liver masses in pregnancy reported three additional cases of HCC [102].…”
Section: Hepatocellular Carcinoma During Pregnancymentioning
confidence: 99%
“…Aflatoxin in the diet may also be a risk factor for HCC [104]. In 1995, Lau and coworkers [101] reported five cases of HCC during pregnancy and reviewed case reports of 23 additional cases. Among the 25 patients with known racial origin, 8 were Chinese and 6 were Nigerian.…”
Section: Risk Factorsmentioning
confidence: 99%